Designers' guide to Eurocode 4 : design of composite steel and concrete structures : EN 1994-1-1 - Johnson, R. P. (ICE, 2012)
EN 1994, or Eurocode 4, specifies the principles and rules for safety, serviceability and durability of composite steel and concrete structures.
Keywords: EN1994 Eurocode 4 (Standard); elektronické knihy; electronic books